Digital competences and collaborative skills among university students - Sandra Salazar Palomino; Yersi-Luis Huamán-Romaní; Carlos Alfredo Bocanegra García; Zany Sigrid Frisancho Triveño; Yajhayda Bellido Ascarza; Alexis León Ramírez; Calixto Cañari Otero (Heritage and Sustainable Development)
Digital competences as the use of ICT after the COVID-19 era had a very significant effect, especially in the education sector, with which university students learned to use and collaborate academically through digital platforms or media. This research work aims to analyze and describe digital competences and their collaborative attitudes in university students. The method used is descriptive research, with a quantitative approach. 1073 university students participated in a survey with questions whose answers were evaluated with the Likert scale. Resulting in the favorite place to use the Internet after home is any place because they have a device (mobile phone), which in the long term would bring consequences to visual and mental health. Despite this negative point, the university is the third favorite place that helps students greatly in academic work. In conclusion, university students successfully learned digital competences and they are taking advantage of it in their academic affairs and do work in a very collaborative way.